Chloride imbalance in Fragile X syndrome - Miles, Kaleb Dee; Doll, Caleb Andrew (Frontiers in Neuroscience, 2022)
Developmental changes in ionic balance are associated with crucial hallmarks in neural circuit formation, including changes in excitation and inhibition, neurogenesis, and synaptogenesis. Neuronal excitability is largely mediated by ionic concentrations inside and outside of the cell, and chloride (Cl-) ions are highly influential in early neurodevelopmental events. For example, γ-aminobutyric acid (GABA) is the main inhibitory neurotransmitter of the mature central nervous system (CNS). However, during early development GABA can depolarize target neurons, and GABAergic depolarization is implicated in crucial neurodevelopmental processes. This developmental shift of GABAergic neurotransmission from depolarizing to hyperpolarizing output is induced by changes in Cl- gradients, which are generated by the relative expression of Cl- transporters Nkcc1 and Kcc2. Interestingly, the GABA polarity shift is delayed in Fragile X syndrome (FXS) models; FXS is the most common heritable neurodevelopmental disorder. The RNA binding protein FMRP, encoded by the gene Fragile X Messenger Ribonucleoprotein-1 (Fmr1) and absent in FXS, appears to regulate chloride transporter expression. This could dramatically influence FXS phenotypes, as the syndrome is hypothesized to be rooted in defects in neural circuit development and imbalanced excitatory/inhibitory (E/I) neurotransmission. In this perspective, we summarize canonical Cl- transporter expression and investigate altered gene and protein expression of Nkcc1 and Kcc2 in FXS models. We then discuss interactions between Cl- transporters and neurotransmission complexes, and how these links could cause imbalances in inhibitory neurotransmission that may alter mature circuits. Finally, we highlight current therapeutic strategies and promising new directions in targeting Cl- transporter expression in FXS patients.